Case Report: Identification of a Novel Homozygous Mutation in GPD1 Gene of a Chinese Child With Transient Infantile Hypertriglyceridemia - Lin, Haihua; Fang, Youhong; Han, Lin; Chen, Jie; Lou, Jingan; Yu, Jindan (Frontiers in Genetics, 2021)
Transient infantile hypertriglyceridemia is a rare autosomal recessive disorder characterized by hypertriglyceridemia, hypohepatia, hepatomegaly, hepatic steatosis and fibrosis in infancy. Mutations in GPD1 gene are considered the causative factor but the underlying mechanism of this disorder is still enigmatic. To date, only 24 different GPD1 mutations have been reported in the literature worldwide with transient infantile hypertriglyceridemia or relevant conditions. Here we report a Chinese girl who developed hepatomegaly, elevated transaminase and hypertriglyceridemia from the age of 4 months. A novel homozygous variant c.454C>T (p.Q152*) was found in GPD1 gene by next-generation sequencing. This patient is the 3rd Asian reported with transient infantile hypertriglyceridemia. We summarized the clinical presentations of transient infantile hypertriglyceridemia and also expanded the spectrum of disease-causing mutations in GPD1.